Artificial propagation and embryonic growth in Stinging catfish, Heteropneustes fossilis (Bloch, 1794) using S-GnRHa (salmon gonadotropin releasing hormone analogue) - Tasrick Araf; Alal Hossain; Gourab Chowdhury; Mohammad Amzad Hossain; Md. Arifur Rahman; Mohammed Mahbub Iqbal (Journal of Tropical Life Science, 2021)
An experiment was performed to observe the potentiality of synthetic hormone analogue in artificial propagation i.e., the embryonic and larval development of Heteropneustes fossilis. Broodfish were injected with S-GnRHa according to the following concentration: 1, 2.5 and 5 ml kg-1 of body weight (BW) to females and 0.5, 1.125 and 2.5 ml kg-1 BW to males, in treatment groups T1, T2 and T3, respectively each with three replicates. The fishes were ovulated at about 10-11 hours after the hormone injection. Result showed the highest fertilization (83.11Â±1.36) and hatching rate (89.56Â±1.04) in T2, whereas ovulation rate was 100% in all treatment groups. First cleavage was observed in 30 minutes of post-fertilization. Embryonic developmental period sequentially for 2-cell, 4-cell, 8-cell, 16-cell, 32-cell, 64-cell, Morula, Blastula, Gastrula, somatic formation, yolk-plug, twisting movement and pre-hatching were 00:30, 00:45, 01:10, 01:30, 02:00, 02:30, 03:00, 04:00, 06:40, 09:00-18:00, 19:00, 20:00-21:00 and 22:00 hours, respectively. Hatching occurred after 23:00 hours of fertilization. Finally, the current result suggested that S-GnRHa might be an effective synthetic hormone in artificial propagation of H. fossilis.